Influence of Dairy Cows Bedding Material on the Microbial Structure and Antibiotic Resistance Genes of Milk - Wu, Haoming; Wang, Yang; Du, Bingyao; Li, Huiying; Dong, Lei; Hu, Haiyan; Meng, Lu; Zheng, Nan; Wang, Jiaqi (Frontiers in Microbiology, 2022)
The presence of pathogenic bacteria and antibiotic resistance genes (ARGs) in milk are among the most important issues related to the safety of dairy products and the health of consumers. However, despite that dairy cow are housed for long periods of time on different beddings, the effect of different bedding materials on the microbial flora and presence of ARGs is unclear. In this study, the composition of microorganisms, and the presence of pathogenic mastitis bacteria and 33 ARGs targeting seven antibiotics in raw milk produced from farms using sand bedding, rice husk bedding, and recycled manure solids (RMS) bedding were compared by amplicon sequencing and real-time quantitative PCR. The results showed that the microbial composition of milk was related to the microbial flora of bedding. None of the pathogenic mastitis bacteria were detected in milk from cows housed on sand bedding (S-M). The proportion of ARGs was highest in the S-M group, and lowest in the Milk from cows housed on RMS bedding (RMS-M) group. In general, the content of ARGs in RMS-M was the lowest, but that bedding may pose a threat to the breast health of dairy cows.